Investigating Farm Machinery Breakdowns and Service Support System Conditions in Rainfed Rice Areas in Riau Province, Indonesia - Paman, Ujang; Khairizal; Sutriana, Selvia (Asian Journal of Agriculture and Rural Development, 2022)
Farm machinery breakdowns are the most common problems farmers face in field operations. The problems can cause losses of time, power, and money and must therefore be prevented. This research investigates farm machinery breakdowns and loss of machine power, as well as service support conditions in Riau Province, Indonesia. Most data were collected from secondary sources published by the Food Crop and Horticulture Services of Riau Province and the Statistical Bureau of Riau Province. The data on service support facilities were obtained through field visits to service support sites in the province. The number of farm machines, farm power, and machine breakdowns increased during the period 2010–2021. There were different breakdown rates among farm machines and regencies. The highest annual growth was 17.03 percent for water pumps, followed by power threshers (14.41%), and 2-wheel tractors (14.32%). Rokan Hilir Regency had the highest level of machinery breakdowns, reaching 26.93 percent annually. The total loss of machine power was 9,553 hp per year on average or 15.76 percent of the total power of 61,357 hp per year. The availability of service support facilities like workshops and storage sheds was very limited and remained inadequate. A lack of spare parts and mechanics was also found in the surveyed areas of the province.